Enabling Access to Pharmacy Law Teaching during COVID-19: Student Perceptions of MyDispense and Assessment Outcomes - Natasha Slater; Thuy Mason; Ricarda Micallef; Madhvee Ramkhelawon; Leanne May (MDPI AG, 2023)
During the COVID-19 pandemic, it was not always possible to teach pharmacy practice and practical dispensing skills in person. Second-year pharmacy students (n = 147) were given access to a virtual simulation tool, MyDispense, to supplement their learning. This software enabled students to work remotely and access exercises in a 'safe' community pharmacy setting. This study evaluated second-year pharmacy students' perceptions of MyDispense, and the impact on assessment performance in the pharmacy law and ethics module. Students were able to access 22 MyDispense activities throughout the academic year (2020/2021). Exercise completion rates and assessment marks were analysed, along with findings from a cross-sectional survey about user experience. MyDispense data were available for all students (n = 147), and 76.1% (n = 115) completed the survey. The mean number of MyDispense exercises completed was nine. Higher levels of MyDispense exercise completion were associated with higher pass rates and mean scores (no exercises completed versus 1-10 activities completed: mean score 77.1 versus 83.1, respectively) and a statistically significant association between exercise usage and in-class assessed prescription scores. Overall, 46.1% (n = 53/115), 33.0% (n = 38/115) and 33.9% (n = 39/115) of students felt that MyDispense had helped them to prepare for their assessed prescriptions, mid-module test, and final exam, respectively. MyDispense has provided an accessible alternative to in-person teaching for students during the COVID-19 pandemic, and results showed a positive association with assessment performance in pharmacy law and ethics.